2020
DOI: 10.1093/femsle/fnaa209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio parahaemolyticus strains isolated from clinically asymptomatic seafood workers

Abstract: Vibrio parahaemolyticus (VP) is a major cause of gastroenteritis outbreaks in Thailand and other countries due to the consumption of contaminated and undercooked seafood. However, there have been few reports of the molecular epidemiology of VP isolates from asymptomatic seafood handlers. Here, we report the phenotypic and genetic characterization of 61 VP isolates obtained from asymptomatic workers in two seafood-processing plants. We found 24 O:K serotypes, of which O11:KUT, O1:KUT and O3:KUT were the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In Escherichia coli , bacteriophage-mediated horizontal gene transfer plays a vital role in the evolutionary selection that leads to the emergence of new commensal strains in the mouse gut ( 38 ). A previous study showed that asymptomatic humans can be reservoirs of V. parahaemolyticus with various serotypically different strains ( 39 ). In this study, the genetically diverse V. parahaemolyticus isolates identified in bird feces possibly occurred as a consequence of the biological and physiochemical conditions of the avian gut, which may enhance horizontal gene transfer among inhabiting bacteria and contribute to the emergence of new strains.…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli , bacteriophage-mediated horizontal gene transfer plays a vital role in the evolutionary selection that leads to the emergence of new commensal strains in the mouse gut ( 38 ). A previous study showed that asymptomatic humans can be reservoirs of V. parahaemolyticus with various serotypically different strains ( 39 ). In this study, the genetically diverse V. parahaemolyticus isolates identified in bird feces possibly occurred as a consequence of the biological and physiochemical conditions of the avian gut, which may enhance horizontal gene transfer among inhabiting bacteria and contribute to the emergence of new strains.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the prevalence of V. parahaemolyticus in food handlers was reported to be 0.3% (17/450), with three isolates being Kanagawa phenomenon positive (Nishlo et al., 1969). In 2002–2003, the presence of pathogenic strains of V. parahaemolyticus among asymptomatic workers in shrimp processing plants in Thailand was nearly 35% (25.8% tdh + trh −; 4.8% tdh − trh +; 4.8% tdh + trh +) (Chonsin et al., 2021). Additionally, a phylogenetic study using multilocus sequencing typing analyzed strains of V. parahaemolyticus from Thailand recovered from various sources associated with the seafood industry, including clinical samples, healthy workers, fresh seafood, frozen shrimp, farmed shrimp tissues, and pond water for shrimp culture.…”
Section: Contamination Routes Of Processed Seafoodmentioning
confidence: 99%
“…Aside from poor handling practices, seafood handlers themselves can represent a source of contamination due to their health status and asymptomatic carriage of human pathogenic Vibrio spp. (Chonsin et al, 2021). In May 2013, 99 employees of a company in Guangdong, China, contracted a co-infection with V. parahaemolyticus and norovirus after consuming roast duck, an uncommon vector for these two pathogens.…”
Section: Food Handlersmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] As one of the most common food-borne pathogenic bacteria, it is always present in clam, shellsh, and other kinds of seafood. 4,5 Aer being consumed, V. parahaemolyticus causes acute gastroenteritis, sepsis, and other diseases, which have common symptoms of vomiting, diarrhea and intestinal cramps. Severe cases can lead to dehydration, shock, or even death.…”
Section: Introductionmentioning
confidence: 99%